Amniotic Fluid. Sex genetic diagnosis, clinical experience. - Fernández Molinari, Luis (2015)
The human genetic sex presents asymmetry in male and female symmetry, making it the first contains 22 autosomes and a pair of heterocromosomas, and verified receive some sperm meiosis and other X chromosome Y.